The Influence of a Particular Kind of Fertilizer Field Entomologist on Growth and Production of Some Hybrid Cron Variety (Zea mays L.) - Roupahim, Roupahim; Siti Aminah,, Iin; Gusmiatun, Gusmiatun (Universitas Muhammadiyah Palembang, 2016)
The Influence of a Particular Kind of Fertilizer Field Entomologist on Growth and Production of SomeHybrid Cron Variety (Zea mays L.). This study aims to: study and evaluate the effect of biological fertilizerswith particular variety on growth and yield of maize (Zea mays L.). This research was conducted at theexperimental farm of the Faculty of Agriculture Campus C Muhammadiyah University of Palembang Hamlet1 Semambu Island Village District of North Indralaya Ogan Ilir South Sumatra. In December 2014 until March2015. This study used a draft Plots Divided (Split-plot Design). The treatment is performed on each subplot isthe type of biological fertilizer and of some variety with 3 replications. Variables observed consisted of: HighPlant (cm), Total Leaves (strands), Weight Cob (g), length seeded Cob (cm), Cob Diameter (cm), Weight 100Corn seeds (g), Berangkas Corn Dry Weight ( g), and Yield Per Plots (kg) The results of this study indicatethat although provision of fertilizer Variety and biological Mikoriza, give the best results on the growth andproduction of hybrid corn maize (Zea mays L) with the highest yield (9, 54 ton / ha) Variety Bisi 2 andMikoriza.